PENGARUH WARNA LIGHT EMITTING DIODE (LED) TERHADAP MORFOGENESIS EKSPLAN KALUS ASAL BULBIL BAWANG PUTIH SANGGA SEMBALUN SECARA IN-VITRO - Ramadani, Sindi; Kristina, Nilla; Syarif, Auzar; Resigia, Elara (Jurnal Agroteknologi, 2024)
The quality of the Garlic seed bulbs needs to be improved by seed propagation through tissue culture techniques to get uniform and big cloves. Utilizing the suitable color spectrum of light is one way to stimulate plant morphogenesis. This study aimed to identify the influence of light color and obtain the best color in the morphogenesis of garlic callus explants. This research was carried out from June to September 2022 at the Tissue Culture Laboratory, Faculty of Agriculture, Universitas Andalas. This study used a completely randomized design with three treatment levels: red, blue, and white. The F test analyzed observational data at a 5% level, followed by Duncan's multiple Range Test (DNMRT) at a 5% level. The results showed light color influences embryogenic callus formation and shoot formation from garlic callus explants. Blue light is better than red and white light in inducing embryogenic callus, increasing the rate of explants forming shoots but giving no significant difference in the length of the shoot.